Influence of strategic inventory on the equilibrium of two competing supply chains. Issue 1 (3rd January 2022) - Saha, Subrata; Nielsen, Izabela Ewa; Sarmah, S. P.
Abstract: In this article, the influence of using strategic inventory and forming collusion between upstream manufacturers and downstream retailers is studied when two competing supply chains offer substitutable products in a common market through exclusive retailers. The optimal pricing decisions are explored in five different scenarios. It is found that with a specific limit of holding cost, the retailer can carry inventory strategically for the benefit of each member when upstream manufacturers have a first-mover advantage. Two-period planning can outperform a single-period decision. However, if two downstream retailers form collusion and uphold strategic inventory, the profit share of upstream manufacturers can reduce considerably, but the sales volume of both supply chains increased. In that circumstance, retailers rely upon more strategic inventory, and manufacturers need to drop their respective wholesale prices considerably in the second period. A long-term wholesale price commitment contract is used to safeguard the interest of upstream manufacturers. We find that the proposed mechanism can improve the performance of all the members. Numerical experiments provide valuable managerial insights regarding the supply chain members' strategic decisions under competition.